Dental teaching faculty involvement in research activities - Dolar Doshi; Jagadeeswara Rao Sukhabogi; Jenisha Patel; D Satyanarayana; Parupalli Karunakar (Wolters Kluwer Medknow Publications, 2023)
Purpose: This study aimed to examine personal and professional factors in determining the research activity and research culture among dental teaching faculty members in Hyderabad City, Telangana. Materials and Method: Two dental schools with ongoing dental undergraduate and postgraduate programmes were included in the study. The Research and Development (R&D) Culture Index Questionnaire comprising 16 items was employed for this study. Also, self-reported research activity undertaken in the past twelve months was recorded. The association of demographic variables and professionally related variables with the perception of R&D culture and participation in research activities was assessed using the Chi-square test. A P value was set at 0.05. Results: Of the one-hundred and fifteen faculty members who participated in the study, seventy-four (64.4%) worked in the government sector and forty-one (35.6%) in privately funded dental college. The mean age of the study population was 34.11 + 7.13 years. The majority of them presented a paper or poster at the conference (66.1%; 76) followed by publishing paper in peer-review journal (42.6%; 49) and grant application for research (6.1%; 7), and authoring of a textbook was undertaken by only 2.6% of the study population. Males (61.1%; P = 0.04) and those employed in private dental college (65.8%; P = 0.02) had significantly high levels of overall perception than their respective counterparts. Conclusion: Our study concludes that this study population has a positive perception (50.32 + 6.95) towards research with the majority of them having done a paper or poster publication (66.1%) in the last one year.